Egypt after the spring revolt and reaction - Hoyakem, Emile; Taha, Hebatalla; Institute of International and Strategic Studies (United Kingdom : The International Institute for Strategic Studies, 2016)
'This Adelphi volume brings together senior scholars as well as rising analysts of Egypt to examine the tumultuous period from the January 2011 uprising against Hosni Mubarak, via the election and ouster of Muhammad Morsi, to the consolidation of presidential power under Abdel Fattah Al-Sisi by late 2015. The nine authors provide a sober, in-depth look at the country's contested politics, institutional and political players, struggling economy, constant foreign policy and evolving security challenges.' --Back cover.
Introduction / Emile Hokayem --The transition: from Mubarak's fall to the 2014 presidential election / Nathan J. Brown --Courts and police in revolution / Ellis Goldberg --The military / Dr. Zeinab Abul-Magd --The Muslim Brotherhood / Yasser El-Shimy --Egypt's non-Islamist parties / Michael Wahid Hanna --Civil society / Dr. H.A. Hellyer --A revolution without a revolutionary foreign policy / Gamal Hassan --Militarisation and security challenges in Egypt / Hebatalla Taha --The Egyptian economy / Mohamed El Dahshan.
Includes bibliographical references and index.
Keywords: Egypt -- Politics and government -- 21st century; Egypt -- History -- Protests, 2011-; Egypt -- Foreign relations -- 21st century; Egypt -- Social conditions -- 21st century; Egypt -- Economic conditions -- 21st century